The effect of combined antihypertensive therapy on left ventricular diastolic function in resting and postexercise patients with arterial hypertension - M. Yu. Kolesnyk (Zaporozhye State Medical University, 2015)
The correction of left ventricular diastolic function abnormalities hasn't been well investigated in arterial hypertension. The aim of the study was to determine the effects of two antihypertensive combinations (perindopril/amlodipine and losartan/amlodipine) on the state of diastolic function at rest and after exercise in patients with arterial hypertension. Results. The early diastolic transmitral flow velocity and mitral annular tissue doppler velocities increased under fixed-dose combination of perindopril and amlodipine. The combination shortened the transmitral E-wave deceleration time and isovolumetric left ventricular relaxation time. The prevalence of diastolic dysfunction decreased from 55.8% to 31% on therapy with perindopril and amlodipine (p<0.05). The treatment reduced the frequency of pathologic results of diastolic exercise stress test. These changes were associated with improved exercise tolerance. Therapy with amlodipine and losartan shortened the deceleration time of early diastolic flow at rest and after exercise. The combination of amlodipine and losartan hasn't reduced the prevalence of left ventricular diastolic dysfunction and hasn't improved exercise tolerance. Conclusions. The six-month treatment with fixed-dose combination of perindopril and amlodipine has a pronounced effect on improving ofLV diastolic function compared with a combination of losartan and amlodipine.